2014
DOI: 10.1007/s11266-014-9531-5
|View full text |Cite
|
Sign up to set email alerts
|

Surreptitious Symbiosis: Engagement Between Activists and NGOs

Abstract: Based on research conducted in Athens, Cairo, London and Yerevan the article analyses the relationship between activists engaged in street protests or direct action since 2011 and NGOs. It examines how activists relate to NGOs and whether it is possible to do sustained activism to bring about social change without becoming part of a 'civil society industry'. The article argues that while at first glance NGOs seem disconnected from recent street activism, and activists distance themselves from NGOs, the situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We found that there was a range of interactions between activists and VOs in London, as indeed in our other field sites (Glasius and Ishkanian, 2015). Some activists spoke positively about their interactions with VOs, describing how they relied on VOs for meeting space, printing services, and research expertise.…”
Section: Dissensus Vs Consensus: Relations Between Activists and Volsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that there was a range of interactions between activists and VOs in London, as indeed in our other field sites (Glasius and Ishkanian, 2015). Some activists spoke positively about their interactions with VOs, describing how they relied on VOs for meeting space, printing services, and research expertise.…”
Section: Dissensus Vs Consensus: Relations Between Activists and Volsupporting
confidence: 74%
“…In the UK context, 'NGO' commonly refers to organisations that work in international development, whereas 'VO' is used to refer to organisations that work domestically. VOs are dependent on funding from governments and international organisations that tend to perceive direct action and political positions as inappropriate and unprofessional (Eikenberry, 2009, Glasius andIshkanian, 2015). This article contributes to these aforementioned literatures by not only examining the politics, demands, practices, and stances of activists working in grassroots groups, but also analysing how those in turn shape activists' views of and relations with formal VOs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus on the surface the protest groups in the former socialist countries may appear to share similarities with movements beyond the region, there are also key differences. For example, several Occupy movements emerged in the postsocialist countries in 2012, including Occupy Mashtots Park in Armenia, Occupy Abai in Russia, and Occupy Slovenia, while they challenged the lack of democracy and growing corruption and oligarchic rule in their respective countries, unlike their North American or Western European Occupy counterparts, these movements also shied away from embracing an overtly left critique or vocal anti-capitalist stance (Glasius and Ishkanian 2015). This reluctance is partly due to the toxic legacy of state socialism which still makes it very difficult for activists to formulate a left discourse or critique of capitalism (Razsa and Kurnik, 2012) (Ishkanian 2015 Mining, Neoliberalism and Civil Society Resistance…”
Section: Introductionmentioning
confidence: 99%
“…However, subversive practices lurk beneath apparent co‐optation. Within and despite neoliberal structures, such practices contribute to interstitial and symbiotic transformations of neoliberalization (Bondi ; Glasius and Ishkanian ; Meade ; Panelli and Larner ; Trudeau ). This paper proposes a framework for two purposes: analysing and informing third‐sector practices for transformation.…”
Section: Social Change Through the Third Sector? Towards A Framework mentioning
confidence: 99%